Study of temporal variability on sugarcane production in the municipality of Pedras de Fogo, Paraíba (2003-2024) - Cruz, Raíres Liliane de Oliveira; Silva, Wemerson Leonardo Cruz da; Oliveira, Ana Cecília da Rocha; Isidro, Renato; Ferreira, Maria Luana Lima; Sousa, Welinagila Grangeiro de; Sousa, Luiz Henrique Guedes; Cordeiro, Maria Eduarda Bezerra Alves; Silva, João Nathan; Oliveira, Robério de; Silva, Wanderlecio Rodrigues da; Silva, Jheison Yan Santana da; et al. (Brazilian Journal of Production Engineering, 2025)
Sugarcane plays an important role in the agricultural economy of Pedras de Fogo, Paraíba, contributing to the economy in terms of generating jobs and income in the region. However, its production has been affected by challenges such as climate variations and traditional agricultural practices. The objective of this study was to analyze the productive dynamics of sugarcane in the municipality of Pedras de Fogo, PB, between 2004 and 2023, seeking to understand the factors that influence this production chain and offer subsidies for local development actions. The methodology consisted of analysis through a database, evaluating the variables: planted area, harvested area, quantity produced, productivity and production value. The results revealed a significant reduction in the cultivated area, which went from approximately 30.000 hectares (ha), in 2004 to approximately 18.000 ha in 2023, with emphasis on 2019, which presented the lowest production. Despite the reduction in area, a trend towards increased production was observed, reflected in the stability of productivity throughout much of the period. Therefore, to ensure the sustainability of the activity, it is necessary to invest in more efficient agricultural practices, adoption of technologies, adequate irrigation management and strengthening of public policies that support local producers.